Study on imperative factors of continuous improvement tool – total productive lean manufacturing for improvement of organisational culture towards world class performance. (1st January 2014) - Muthukumar, N.; Tamizhjyothi, K.; Resmi, A.T.; Nachiappan, R.M.
Continuous improvement (CI) tools – total productive maintenance (TPM) and lean manufacturing (LM) have been adopted for the management of machines (process) and the product line (flow/speed) respectively throughout the world. The TPM and LM philosophies have been adopted in the context of continuous improvement, but nearly always separately (without integration) and with little understanding of their influence on cultural and performance indicators of organisation. This study explores the imperative factors of improvement (CI) tool – total productive lean manufacturing (CI tool – TPLM) and investigates the influence of CI tool – TPLM on organisational culture indicators. From the analysis, it is observed that there is a considerable positive change in all the cultural indicators (CPIs), which show the imperative factors of CI tool – TPLM have consequences and relationship on the cultural and performance indicators of organisations towards world class level. Therefore, the organisations which have not implemented CI tool – TPLM are recommended for implementing the integrated CI tool towards change in organisational culture indicators and achieve the world class performance in manufacturing.